Qualidade de processamento e tempo de armazenamento dos tubérculos de clones de batata - Ubessi, Cassiane (2015)
Potato tubers are used as food and seed. Post-harvest conditions affect tubers for both usages, since physiological changes occur during tuber storage. The objective of this work was to assess the processing quality and time until tuber sprouting of advanced clones of potato. We evaluate thirteen clones and two check varieties of potato in a storage room at 10ºC in two years. The processing quality was evaluated right before loading and after 30, 60, 90 and 120 days of storage for the fresh and dry weight content, chip color and reduced sugars. The experiment was a factorial of clone and storage time in the complete random design, with four repetitions. The percentage of fresh weight loss increased over time during storage, mainly at 120 days. The assessed clones presented dry weight content between 17.4% to 25.2 % during the cold storage. Chip color showed an intense yellow tone and acceptable color classification for the processing industry, even with the increase of reduced sugars during storage. The storage at 10 ºC extended in a 100 days the sprout process. The refrigerated storage promote physiological changes on the tubers, but this changes don´t compromise the use in the industry processing and also allows to increase the storability period of the tubers for both consumption and seeds.